Penguatan Profil Pelajar Pancasila Melalui Pembiasaan Siswa di Pagi Hari di SMP Negeri 2 Mojokerto - Khumairotun Nisa; Muhammad Fahmi; Fathur Rohman (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This article discusses the Strengthening of Pancasila Student Profiles through morning habits of students at SMP Negeri 2 Mojokerto. This study uses qualitative research through a descriptive approach. Data collection was carried out using observation, interview, and documentation techniques. Data analysis techniques consist of data collection, data presentation, and conclusions. The results of the study indicate that the character of Pancasila students is strengthened by the regularity of morning habits at SMP Negeri 2 Mojokerto, namely a series of activities to greet students every morning in front of the school gate. In addition, the 5S culture (Smile, Greet, Greeting, Polite, and Courteous) is the foundation in the process of strengthening the character of Pancasila students. Through morning habits, students show a polite and friendly attitude towards teachers when they meet. And the implications of implementing morning habits are that students have a stronger character, are devoted to God Almighty, namely performing the dhuhur prayer in congregation without being told by the teacher, when meeting friends or teachers, greeting each other, and shaking hands. Previously, students had a very indifferent attitude.